LA (LABORATE AGAMA): PILLAR OF MODERNIZATION OF ISLAMIC RELIGIOUS EDUCATION TRADITION AT MA PUTRI NURUL MASYITHOH LUMAJANG - Chasani, Achmad; Muttaqin, Ahmad Ihwanul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Modernization of religious education is a challenge as well as an opportunity for Islamic educational institutions to respond to the dynamics of the times. This article examines the Religious Laboratory (LA) program as a pillar of the modernization of religious traditions and learning at Madrasah Aliyah (MA) Putri Nurul Masyithoh, Lumajang. The LA (Religious Laboratory) program is designed as an innovative approach that combines Islamic boarding school traditions with modern learning methods based on religious laboratories. This program integrates Islamic values with 21st-century skills, such as critical thinking, collaboration, and technological literacy. Through a descriptive qualitative study, this study analyzes the implementation of the program, learning strategies, and their impact on the intellectual and spiritual development of students. The study shows that the LA Program is expected to be able to strengthen religious understanding and also create an interactive, contextual, and relevant learning environment for the needs of the current generation. Thus, this program becomes an adaptive and progressive model of religious learning, contributing to the transformation of Islamic education in the modern era.